Dimensi Normatif Pengelolaan Sampah dalam Sistem Hukum Lingkungan Indonesia: Normative Dimensions of Waste Management in the Indonesian Environmental Legal System - Abdul Rahmat Waladow; Fenty U. Puluhulawa; Julius T. Mandjo (Jurnal Hukum Bisnis, 2026)
This study aims to analyze the normative construction of waste management within the Indonesian environmental legal system by assessing the structure, substance, and coherence of the norms within the legal framework. Using normative legal research methods with a statutory and conceptual approach, data in the form of primary, secondary, and tertiary legal materials were obtained through literature studies and analyzed grammatically, systematically, and teleologically to test their vertical and horizontal consistency and systemic legitimacy. The results of the study indicate that waste management regulations have established a relatively systematic legal framework with a preventive orientation, grounded in the principle of reduction and corrective measures through administrative, civil, and criminal enforcement mechanisms and sanctions, which are conceptually aligned with the principles of sustainability, prudence, and polluters' responsibility. Normatively, this legal construction has been integrated into the national environmental protection and management regime. However, its effectiveness still requires harmonization of derivative regulations and consistent law enforcement to ensure the protection of the right to a good and healthy environment.